2000
DOI: 10.3109/07853890008995950
|View full text |Cite
|
Sign up to set email alerts
|

Low serum insulin-like growth factor-binding protein-1 is associated with an unfavourable cardiovascular risk profile in elderly men

Abstract: Serum insulin-like growth factor-binding protein-1 (IGFBP-1) is regulated by insulin and has been suggested to be a marker of the insulin resistance syndrome. The aim of this study was to investigate whether serum IGFBP-1 is associated with cardiovascular risk factors. Serum insulin-like growth factor-I and IGFBP-3 were also determined. 331 men aged 70-89 years were examined from the Finnish cohort of the Seven Countries Study. Serum IGFBP-1 concentrations were measured by immunofluorometric assay, and the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
0
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 18 publications
4
10
0
2
Order By: Relevance
“…Another cross-sectional study found that lower IGFBP1 levels were associated with known cardiovascular risk factors in 273 adults aged 20-74 years (32). Our results are in keeping with a previous smaller study involving 331 Finnish men aged 70-89 years in which IGFBP1 levels correlated with insulin sensitivity (33). The inverse relationship between IGFBP1 and metabolic syndrome could be explained by its role as a marker of insulin sensitivity, as IGFBP1 correlates closely to whole-body and hepatic insulin sensitivity (34,35).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Another cross-sectional study found that lower IGFBP1 levels were associated with known cardiovascular risk factors in 273 adults aged 20-74 years (32). Our results are in keeping with a previous smaller study involving 331 Finnish men aged 70-89 years in which IGFBP1 levels correlated with insulin sensitivity (33). The inverse relationship between IGFBP1 and metabolic syndrome could be explained by its role as a marker of insulin sensitivity, as IGFBP1 correlates closely to whole-body and hepatic insulin sensitivity (34,35).…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with previous studies in men of varying ages in linking IGFBP1 levels with insulin sensitivity (19,20,32,33). Thus, lower IGFBP1 levels were associated with impaired glucose tolerance in an ethnically diverse sample of 272 adults from Manchester (19) and with metabolic syndrome in 839 adults aged 40-65 years in the Cambridgeshire study (20).…”
Section: Discussionsupporting
confidence: 91%
“…A potential role of IGFs in the pathogenesis of cardiovascular disease has long been recognised. In cross-sectional studies low serum IGFBP-1 levels are associated with an unfavourable cardiovascular risk profile in diabetes and in populations without diabetes [10,11,45,46]. Low IGF-I is also associated with cardiovascular risk factors [45,47], independently of low IGFBP-1 [12,15].…”
Section: Discussionmentioning
confidence: 99%
“…IGF1 and IGFBP1, -2, and -3 are considered components of two axes: the GH/IGF1 axis, including IGF1 and IGFBP3, and the obesity-insulin resistance axis, including IGFBP1 and -2. IGFBP1 and -2 are inversely correlated with insulin and BMI, and are expectedly to be negatively associated with components of insulin resistance syndrome, namely, hypertension, diabetes, and dyslipidemia (24,25). Conversely, the role of IGF1 is less clear.…”
Section: Discussionmentioning
confidence: 99%